Determinasi Mutasi Kerja, Kompensasi dan Pengawasan terhadap Kinerja Karyawan - Reza Safitri (JIAGANIS, 2017)
ABSTRACTThe purpose of this study was to analyze the determination of mutations, compensation and oversight of the performance of employees at PT BPR Dana archipelago. The variables in this study include the independent variables are working mutation (X1) compensation (X2) supervision (X3) and the dependent variable is employee performance (Y). The formulation of the problem in this study is whether the mutation, compensation and oversight is determined to employee performance in PT BPR Dana archipelago.This research uses quantitative data derived from primary data collected through questionnaires. The population in this study were all employees at PT BPR Dana Nusantara many as 210 people and sampling using the formula slovin with a standard error of 5% or 0.05 obtained by 138 people. The data analysis method used is the test instrument testing done by testing the validity and reliability. Data were analyzed using descriptive analysis, multiple linear regression analysis and hypothesis testing.The results showed that in partial mutation is determined significant work on employee performance, compensation is determined significantly to the performance of employees, monitoring the performance of employees is determined significantly. And the results of simultaneous testing of employee performance, compensation and oversight is determined significantly on employee performance. Keywords: Mutations Work, Compensation, Controlling, Employee performance